2009
DOI: 10.1258/jhsrp.2009.008128
|View full text |Cite
|
Sign up to set email alerts
|

‘There are too many of us to fix.’ Patients’ views of acceptable waiting times for hip and knee replacement

Abstract: Patients' views of acceptable waiting times are important for a fair process of establishing waiting time benchmarks for joint replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…Waiting for health services that are more fundamental for acceptable survival in everyday life, like cataract or hip and knee replacement surgery, could be expected to cause more inconvenience. The maximum acceptable waiting times for such surgery is similar to or even longer [14][15][16][17] than that expressed by dental patients in the present study. This discrepancy can be interpreted as an indication that dental services are relatively highly valued by patients.…”
Section: Discussionsupporting
confidence: 72%
“…Waiting for health services that are more fundamental for acceptable survival in everyday life, like cataract or hip and knee replacement surgery, could be expected to cause more inconvenience. The maximum acceptable waiting times for such surgery is similar to or even longer [14][15][16][17] than that expressed by dental patients in the present study. This discrepancy can be interpreted as an indication that dental services are relatively highly valued by patients.…”
Section: Discussionsupporting
confidence: 72%
“…Not only were participants in this study satisfied with the service they received while waiting for THR and TKR, they displayed a degree of altruism consistent with other patient groups [27][28][29][30]. Patient satisfaction was found to be associated with the period of waiting for an initial consultation, which to date has been overlooked in the establishment of waiting time targets in Australia.…”
Section: Resultssupporting
confidence: 52%
“…Conner-Spady et al [4] found that patients thought that the maximum acceptable waiting time should be 4 months, well below the actual times found in this study. Conner-Spady et al…”
Section: Fig 1 Findings From the Hospital List With Average Age Andcontrasting
confidence: 65%
“…[6] One study found that 84% of waiting patients felt that it was fair if another patient was placed ahead of them if they had worse pain or greater limitation of daily functions. [4] However, Tebé et al [7] reported on primary knee arthroplasty waiting lists and concluded that the priority system had no effect on implementing prioritisation for patients based on their severity.…”
Section: Fig 1 Findings From the Hospital List With Average Age Andmentioning
confidence: 99%
See 1 more Smart Citation